Peningkatan Kemampuan Cara Berfikir Siswa Terhadap Belajar Literasi Dan Numerasi SDN 010 Melayu Besar Melalui Program Kampus Mengajar Angkatan III - Rita Yusreni Nainggolan; Adi Suarman Situmorang; Eka Putri Saptari Wulan; Nelly Karlina; Yurianti Yurianti (TRIDHARMADIMAS: Jurnal Pengabdian Kepada Masyarakat Jayakarta, 2022)
Independent Campus Teaching and Learning Program (MBKM) organized by the Ministry of Education and Culture. The Campus Teaching Program is currently the third batch assigned to teach, assist with technology, and assist school and teacher administration. One of the schools that became the location of the Teaching Campus is SDN 010 Melayu Besar which is located in Permai Village, Tanah Putih District, Tanjung Melawan, Rokan Hilir Regency, Riau Province. The aims of this Teaching Campus include increasing empathy or social sensitivity to existing problems, honing thinking skills, collaborating, developing insight, character, and soft skills, increasing the role and contribution and dedication of students from the academic community to national education. This Teaching Campus activity is carried out for approximately 4 months which supports students in implementing the Teaching Campus program directly into the real world. In this activity students help teachers teach, adapt technology, and assist school administration and teachers. and from the results of these experiences, the authors can conclude that this program is very useful for teachers or schools, where this program is beneficial and also beneficial for students.